Artikel Review : Pengaruh Perbedaan Bahan Pengikat Sintesis dan Alami dalam Sediaan Tablet Hisap - Annisa Annisa; Khusnul Khotimah; Nabila Sativa; Noor Kamalliyah; Siti Nor Adidah; Nor Latifah (An-Najat, 2024)
A lozenge is a form of solid pharmaceutical preparation designed to dissolve slowly in the oral cavity, providing both local and systemic effects. In lozenge formulation, binders play an important role in ensuring tablet hardness and appropriate dissolution time. This study aims to compare the effects of synthetic and natural binders on the physical properties and performance of lozenges. Synthetic binders such as PVP, CMC Na, and Hydroxypropyl Methylcellulose (HPMC) tend to provide higher tablet hardness and more controlled dissolution times. Meanwhile, natural binders such as maltodextrin, gum arabic, and jackfruit seed starch show good abilities to enhance tablet cohesion, with the additional benefits of biocompatibility and biodegradability. The research results indicate that synthetic binders provide better physical stability, while natural binders are preferred due to their environmentally friendly properties and ability to improve patient acceptance.